Bipolar Disorder: Role of Inflammation and the Development of Disease Biomarkers - Muneer, Ather (Psychiatry Investig, 2016)
Bipolar disorder is a severe and enduring psychiatric condition which in many cases starts during early adulthood and follows a relapsing and remitting course throughout life. In many patients the disease follows a progressive path with brief periods of inter-episode recovery, sub-threshold symptoms, treatment resistance and increasing functional impairment in the biopsychosocial domains. Knowledge about the neurobiology of bipolar disorder is increasing steadily and evidence from several lines of research implicates immuno-inflammatory mechanisms in the brain and periphery in the etiopathogenesis of this illness and its comorbidities. The main findings are an increase in the levels of proinflammatory cytokines during acute episodes with a decrease in neurotrophic support. Related to these factors are glial cell dysfunction, neuro-endocrine abnormalities and neurotransmitter aberrations which together cause plastic changes in the mood regulating areas of the brain and neuroprogression of the bipolar diathesis. Research in the above mentioned areas is providing an opportunity to discover novel biomarkers for the disease and the field is reaching a point where major breakthroughs can be expected in the not too distant future. It is hoped that with new discoveries fresh avenues will be found to better treat an otherwise recalcitrant disease.